Computation of dispersion diagrams for periodic porous materials modeled as equivalent fluids. (August 2020) - Magliacano, Dario; Ouisse, Morvan; Khelif, Abdelkrim; De Rosa, Sergio; Franco, Francesco; Atalla, Noureddine; Collet, Manuel
Abstract: The application of shift cell technique is presented and discussed for periodic porous media described with equivalent fluid models: as it can be found in literature, it consists in a reformulation of classical Floquet-Bloch (F-B) conditions, in which the phase shift of the boundary conditions, related to wave propagation, is integrated into the partial derivative operator. Consequently, the periodicity is included in the overall behavior of the structure, while continuity conditions are imposed at the edges of the unit cell. Its major advantage stands in allowing the introduction of a generic frequency dependence of porous material behavior, through the resolution a quadratic eigenvalue problem, providing an efficient way to compute the dispersion curves of a porous material modeled as an equivalent fluid. A validation and a computational cost comparison are performed between the shift cell technique and the classical F-B approach, pointing out that the first can provide, among its other advantages, a sensible computational time reduction for this kind of analyses. The derivation of the equivalent acoustic properties of the unit cell from its dispersion characteristics is also investigated. To this aim, group velocity matrix formulation and a branch-tracking algorithm are described. Some test cases are used for validating the proposed methodology.